2018
DOI: 10.17221/19/2016-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Measuring technical efficiency of Thai rubber production using the three-stage data envelopment analysis

Abstract: Krause J., Machek O. (2018): A comparative analysis of organic and conventional farmers in the Czech Republic. Agric. Econ. -Czech, 64: 1-8. Abstract:Organic farming has become a topic that receives an increasing academic as well as popular attention. Th is study examines the fi nancial diff erences between the organic and conventional farmers, as well as their income volatility. Based on the Student's t-test, the regression analysis and the matched-pair investigation on a sample of Czech 291 organic and 4045 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
0
10
0
1
Order By: Relevance
“…It is suggested that extension workers visit farmers to guide them in the best practices for managing inputs. This could result in the enhancement of technical, allocative, and economic efficiency for these rice farmers and thus increase production and yield to meet food security needs, which is the most important issue worldwide [31]. We recommend the following.…”
Section: Technical Efficiencymentioning
confidence: 99%
“…It is suggested that extension workers visit farmers to guide them in the best practices for managing inputs. This could result in the enhancement of technical, allocative, and economic efficiency for these rice farmers and thus increase production and yield to meet food security needs, which is the most important issue worldwide [31]. We recommend the following.…”
Section: Technical Efficiencymentioning
confidence: 99%
“…Charnes et al (1978) presented a way of solving this function using the concept of Farell and Fieldhouse (1962), who were the first to attempt to use linear programming to measure efficiency (Førsund and Sarafoglou, 2002;Chang and Guh, 1991). Detailed information on the DEA method has been presented, among others, in the publications by Banker et al (1984), Cooper et al (2006), Zijiang (2006), Kočišová (2016), Parichatnon et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Analytical Hierarchy Process (AHP) method [4] was employed to determine service criteria quality in rice mills which then used to measure efficiency in further method. Data Envelopment Analysis method was employed to determine efficient relativity [6] in defining efficient rice mill location.…”
Section: Methodsmentioning
confidence: 99%